Strategic risk management: an overview - Andersen, Torben J. (Henry Stewart Talks, 2012)
Why care about risk, Examples of risk, Different types of risk, Risk governance focus, Uncertainty and 'unknowability', The changing risk landscape, Risk management cycle, Systematic search for major risks, Risk scenarios, Risk assessment and prioritization, Risk management principles, Enterprise risk management, Structure and culture, Strategic risk management, Integrative risk management, Risk management effectiveness and perceptions, Creating value, Honing the risk potential, Successful risk taking, Centralization and decentralization, Organizing risk responses, The chief risk officer, The risk management office, Ongoing challenges
Reviewed at 2017/07/31